PEMAHAMAN KONSEP QANA’AH DALAM MENYIKAPI FEAR OF MISSING OUT (FoMO) PADA GENERASI Z MUSLIMAH PENGGUNA MEDIA SOSIAL - Fatihatul Aulia; Agus Sukirno; Deni Iriyadi (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2026)
The development of digital technology and the increasing use of social media among Generation Z have given rise to various psychological phenomena, one of which is Fear of Missing Out (FoMO). FoMO is a feeling of anxiety or fear of missing out on information, experiences, or activities experienced by others, especially those seen through social media. This condition can trigger social comparison, anxiety, and reduce an individual’s psychological well-being. From an Islamic perspective, the concept of contentment is seen as a spiritual value that emphasizes feelings of sufficiency, gratitude, and acceptance of Allah SWT’s provisions. This study aims to understand how understanding the concept of contentment plays a role in reducing FoMO experiences among Generation Z Muslim women who use social media. This study uses a qualitative approach with a phenomenological type to explore the subjective experiences of informants. The research subjects were selected using a purposive sampling technique with the criteria of Muslim women belonging to Generation Z, active users of social media, and having experiences related to FoMO. Data collection was conducted through in-depth interviews, observation, and documentation. Data were analyzed using phenomenological analysis which includes transcription, data reduction, thematic coding, and identification of main themes. The results of this study indicate that FoMO experiences among Generation Z Muslim women manifest as anxiety about missing out on information, a compulsion to constantly monitor social media, and a tendency to compare themselves to others. Factors influencing FoMO include the intensity of social media use, the psychological need for social acceptance, and the tendency to engage in social comparison. Furthermore, understanding the concept of contentment (qana’ah) helps informants control desires, reduce envy, and foster gratitude for what they have. Thus, contentment serves as a spiritual value that can help Generation Z Muslim women use social media more wisely and reduce anxiety associated with the FoMO phenomenon.